Emergency colon surgery - Pertusso, Juan C (Cirugía del Uruguay, 1970)
Urgency surgery of the -colon, poses a double problem to the surgeon: the main d1sease and its complication. Only the most frequent and important organic diseases in adults, are considered. Urgency is justified in cases of occlusion, infection, haemorrhage and ischemia; generally a combination of more than one. Progress in colonic surgery -conceptually and technically- and team work ( which includes an anesthesist and an internist often makes it possible to solve the main disease and its complications in the same surgical act. With respect to cancer in a state of occlusion, it is deemed convenient to effect a primary resection with or without anastomosis. The problems derived thereof, are discussed, as well as the origin of the llmitations which prevent its systematic employment. It is convenient to consider sub-occlusive stages as urgencies. The paper includes statistical figures ( overall) in the Hospital de Clínicas ( University Hospital), of surgeons at Prof. Chifflet's clinic and personal figures of Prof. Cendán Alfonzo; a total of over 260 patients. Pre, intra and post-operatory decompression methods, specially with a view to resection in the acute phase, are analyzed. Cancer perforations are dassified as tumoral, juxta-tumoral and diastasic, and a.equ!te procedures for the treatment of each are discussed, with the accent on the advantages of an aggressive attitude. With respect to spontancous or idiopathic perforations, it is necessary to conduct further research. In this ,category, "effort perforations" are dearly identified. In cases of colonic volvulus, we reject systematic resection and consider that the .ethod should be conditioned to the individual patient, taking into consideration the state of the intestine, etiology and risk. Prof. Cendán's method for fixing sigmoids is described. The death-rate in cases of strangled hernation with ,colonic contents, is due to closed occlusions behind. Herniation-cancer relations are discussed. In cases of colonic wounds, we support primary suture, subject to the conditions already established by national authors. íl(i The paper includes sone cases of colon.c invagination, showing tumor predominance in its ethiology and participation of iatrogenia in its production. Apendicitis cancer relationship and cancer inflamatory tumefaction are analyzed; right entrance hemicolectomy is indicated HS the most adequate treatment at present. Faecalomas as the cause of obstructions, present problems which differ according to their ethiology and topography. Cases of patients suffering from this disease treated at the Hospital de Clínicas ( University Hospital), are revised. Colonic occlusion due to bands or postoperatory adhesions are discussed; they show predominance of surgery of the urogenital system. Colonic repercussions of urogenital cancers -caused either by infiltration or radiotherapy- are severe and com Acute complications of diverti ·ular disease and ulcerous colitis will be discussed by Drs. Mautone and Gutiérrez Blanco.